Acanthosis Nigricans Associated with Morbid Obesity and Colorectal Adenocarcinoma - Li, J. (Hindawi Publishing Corporation, 2012)
We report a case of a morbidly obese 32-year-old man presenting with acanthosis nigricans in the setting of Duke's B adenocarcinoma of the hepatic flexure.